Students’ Perceptions of Using E-Portfolio in Learning Language Material Development at Universitas Muhammadiyah Makassar: A Descriptive Qualitative Research - Vera Hidayati; Herlina Daddi; Ariana Ariana (PT ARRUS Intelektual Indonesia, 2024)
The use of digital technology in education has driven a shift from traditional paper-based portfolios to electronic portfolios (E-portfolios) that are more efficient, flexible, and have a wider reach. This study aims to explore students' perceptions of the use of E-portfolios in Language Material Development (LMD) learning. This research was conducted qualitatively by involving five eighth-semester students from the English Education Department at Universitas Muhammadiyah Makassar, using a descriptive qualitative method Data were obtained through semi-structured interviews, employing purposive sampling techniques. The results of the study indicate that there is a positive perception of the use of E-portfolios, including ease of access, organization of materials and tasks, and the ability to store large amounts of data. Additionally, the available features help students create a more attractive, easy-to-understand E-portfolio display that is also secure and protects privacy. The electronic devices owned by the student further support and facilitate the process of uploading assignments into E-portfolios. This research is expected to provide a deeper understanding of the effectiveness and impact of using E-portfolios at Universitas Muhammadiyah Makassar.